Penerapan Model Pembelajaran Differentiated Based Learning dalam Meningkatkan Kreativitas Siswa-Siswa di SD IT Darussalam - Sunanih Sunanih; Afifah Avilani; Nabila Destiana; Siti Nabilah Hasna; Fauziah Tazkia Nur; Zahra Aulia Nugraha; Rizva Alvina; Gya Tri Lestari; Sri Purnama Sari; Devi Sri Agustin; Ayu Rahmawati; Fitri Pujiyanti; Chandra Rizky Noviandi (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2025)
This study aims to determine the application of Differentiated-Based Learning (DBL) learning model in improving students' creativity at IT Darussalam Elementary School. DBL is a learning approach that adapts the learning process to the needs, interests and ability levels of each student. This research uses a qualitative approach method with a combination of interviews and direct observation, interviews were conducted with the principal. The results showed that the application of Differentiated-Based Learning (DBL) model can improve students' creativity. Suggestions for the development of the Differentiated-Based Learning model can conduct teacher training, improve learning facilities and infrastructure. SD IT Darussalam is on the right track in developing a learning model that suits the needs of students. To face the challenges, strategic steps such as supervision, collaboration, innovation and the use of technology show the school's commitment to providing quality learning. With continuous support, learning models such as DBL or PBL can be applied more effectively, providing a positive impact on student development, both academically and non-academically